OTIMIZAÇÃO DA SÍNTESE DO PROJETO DE ATUADORES MEMS BASEADOS EM DEFORMAÇÃO ELÁSTICA E ESTRUTURA COMB-DRIVE - Reimbold, Manuel M. P.; Leandro, Gideon V.; Chong, Wang; Ribas, Renato P. (Salão do Conhecimento, 2013)
Resumo